(untitled) (Superficies y Vacío, 2012)
Magnetic spheres were produced by adaptating conventional Ar-He thermal spray processes. This process is based on the projection of different iron oxides-rich powder precursors which are common byproducts of diverse metallurgical industrial activities. Projected particles are trapped inside a special capturing device. Prior to the plasma processing, precursor materials were milled in order to homogenize their initial particle sizes. The produced magnetic particles showed a spherical morphology with different superficial structures. Their composition includes a mixture of crystalline phases that could be indexed to the magnetite (Fe3O4), maghemite (gamma-Fe2O3) and other phases depending on chemical composition of used precursor. Complete characterization of magnetic spheres was achieved by using several analysis techniques such as: X-ray diffraction (XRD), scanning electron microscopy (SEM), field emission scanning electron microscopy (FESEM), X-ray energy dispersive spectroscopy (EDS) and vibrational sample magnetometry (VSM).